A preliminary comparison of cranial and external morphological variability of Southern Crested Newt (Triturus karelinii) from the Crimea and the Caucasus - Pysanets, Y.; Kukushkin, O.; Manuilova, O. (Збірник праць Зоологічного музею, 2014)
The Triturus karelinii group of crested newts comprises the eastern, central and western lineages that differ by mitochondrial DNA. The eastern lineage largely retains the ancestral cranium shape and is distributed throughout the Crimean Peninsula, the Caucasus Isthmus, and the Caspian Sea southern shore in Iran. In this report the comparison of the Crimean and Trascaucasian T. karelinii cranium shape, differences in the dimensional characteristics variability and body colouring patterns is presented. The samples of T. dobrogicus from the Danube River Delta have been employed for outgroup comparison. Data of the differences between several populations within the eastern lineage suggest that it is not uniform and T. karelinii from the Crimean Peninsula is considered to be somewhat different. Група Triturus karelinii з числа гребінчастих тритонів включає східну, центральну і західну гілку, які відрізняються за мітохондріальною ДНК. Східна гілка значною мірою зберігає анцестральну форму черепної коробки і поширюється всім Кримським півостровом, Кавказьким перешийком і південним узбережжям Каспійського моря в Ірані. Проведено порівняння кримської і закавказької черепної форми Т. karelinii, вказано на відмінності мінливості розмірних характеристик і забарвлення тіла. Екземпляри Т. dobrogicus з дельти Дунаю були використані для порівняння. Дані про відмінності між декількома популяціями в межах східної гілки припускають, що вони не є однорідним, і Т. karelinii з Кримського півострова дещо відрізняється. Группа Triturus karelinii гребенчатых тритонов включает восточную, центральную и западную ветвь, которые отличаются митохондриальной ДНК. Восточная ветвь в значительной мере сохраняет анцестральную форму черепной коробки и распространена по всему Крымскому полуострову, Кавказскому перешейку и южному побережью Каспийского моря в Иране. Проведено сравнение крымской и закавказской черепной формы Т. karelinii, указано на отличия изменчивости размерных характеристик и окраски тела. Экземпляры Т. dobrogicus из дельты Дуная были использованы для сравнения. Данные об отличиях между несколькими популяциями в пределах восточной ветви допускают, что они неоднородны, и Т. karelinii с Крымского полуострова несколько отличаются.